The Silent Classroom Phenomenon in Indonesian Language Learning: A Study on Barriers to Students’ Speaking Skills - Joko Setiyono; Moh. Fuadul Matin; Muhamad Sholehhudin (JPI: Jurnal Pustaka Indonesia, 2026)
Speaking skills constitute a crucial competency in Indonesian language learning, as they are closely related to students’ ability to express ideas, construct arguments, and participate in academic discussions. However, in instructional practice, the phenomenon of the silent classroom is frequently observed, referring to a relatively passive classroom condition characterized by low levels of students’ oral participation during lectures. This study aims to describe the silent classroom phenomenon in Indonesian language learning and to analyze the factors contributing to students’ low speaking proficiency. This research employs a descriptive qualitative approach, involving 40 first-semester students of the Indonesian Language and Literature Education Study Program at IKIP PGRI Bojonegoro, enrolled in a speaking skills course. Data were collected through classroom observations, interviews, and documentation, and subsequently analyzed using a data analysis model consisting of data reduction, data display, and conclusion drawing. The findings reveal that students’ speaking participation remains relatively low, with 20% categorized as active participants, 37.5% as moderately active, and 42.5% as passive or silent. The silent classroom phenomenon is influenced by several factors, including low self-confidence, anxiety about speaking in front of the class, limited vocabulary, and prior learning experiences that tend to be passive. In addition, pedagogical factors—such as teaching methods still dominated by lectures, a lack of interactive discussion activities, and insufficient speaking practice—also contribute to the low level of students’ oral participation. These findings underscore the importance of developing more communicative, interactive, and participatory speaking instruction strategies in Indonesian language learning at the tertiary level.